2002
DOI: 10.1111/j.1574-6968.2002.tb11030.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of theSchwanniomyces occidentalis SWA2gene promoter inSaccharomyces cerevisiae

Abstract: The effect of different carbon sources on the expression in Saccharomyces cerevisiae of the SWA2 alpha-amylase gene from Schwanniomyces occidentalis was studied from constructs containing its 5' region (-223 to +15), which were fused in-frame to the lacZ gene coding sequence. Maximal expression was achieved with the non-fermentable substrates ethanol and/or glycerol, whereas lower levels were found with maltose or galactose. In contrast, glucose repressed it, even in the presence of any of these other carbon s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Glucose presence in the medium can induce genes related to glycolysis and fermentative metabolism. However, the presence of another substrate (ethanol) can stimulate genes related to secondary metabolism and repress the use of glucose to obtain hydrolytic enzymes (Carmona et al, 2002). De Deken (1966) indicated that respiratory metabolism after fermentative metabolism is due to energy compensation necessary for cellular growth.…”
Section: Analysis Of the Crabtree Effect On Culture Qualitymentioning
confidence: 99%
“…Glucose presence in the medium can induce genes related to glycolysis and fermentative metabolism. However, the presence of another substrate (ethanol) can stimulate genes related to secondary metabolism and repress the use of glucose to obtain hydrolytic enzymes (Carmona et al, 2002). De Deken (1966) indicated that respiratory metabolism after fermentative metabolism is due to energy compensation necessary for cellular growth.…”
Section: Analysis Of the Crabtree Effect On Culture Qualitymentioning
confidence: 99%